2016
DOI: 10.3390/ijms17050776
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Expression Profile Based on Differentially Expressed Genes in Middle Cerebral Artery Occlusion Animal Models

Abstract: Stroke is one of the most common causes of death, only second to heart disease. Molecular investigations about stroke are in acute shortage nowadays. This study is intended to explore a gene expression profile after brain ischemia reperfusion. Meta-analysis, differential expression analysis, and integrated analysis were employed on an eight microarray series. We explored the functions and pathways of target genes in gene ontology (GO) enrichment analysis and constructed a protein-protein interaction network. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…In terms of YDBS-specific genes, MAPK signaling pathway and Egfr were identified as the hub pathway and gene based on the network analyses. The results are in good agreement with another integrated analysis of expression profile in MCAO animal models, in which MAPK was also enriched as the most significantly pathway [ 37 ]. MAPK has been recognized as a potential therapeutic target for ischemic stroke, activation of MAPK signaling after ischemic stroke has been identified in neuron, astrocyte and microglia [ 38 ], and the inhibition of that has protective effect on ischemic stroke [ 39 ].…”
Section: Discussionsupporting
confidence: 86%
“…In terms of YDBS-specific genes, MAPK signaling pathway and Egfr were identified as the hub pathway and gene based on the network analyses. The results are in good agreement with another integrated analysis of expression profile in MCAO animal models, in which MAPK was also enriched as the most significantly pathway [ 37 ]. MAPK has been recognized as a potential therapeutic target for ischemic stroke, activation of MAPK signaling after ischemic stroke has been identified in neuron, astrocyte and microglia [ 38 ], and the inhibition of that has protective effect on ischemic stroke [ 39 ].…”
Section: Discussionsupporting
confidence: 86%
“…24 Regardless of the relatively small set of common genes across the literature, pathway analyses revealed that MAP kinase signaling was a prominent and common pathway triggered by cerebral ischemia, in agreement with our cell culture findings here. Similar conclusions were reached by Zhou et al., 25 who identified MAP kinase, cytokine-cytokine receptor interactions, and neurotrophin signaling as common pathways in a meta-analysis of four microarray datasets. Again, these pathways were detected in our present study.…”
Section: Discussionsupporting
confidence: 80%
“…A recent study provides proof-of-concept that species differences (rat vs. mouse vs. human) exist in chemokine/cytokine subnetworks in brain cells exposed to oxygen-glucose deprivation that may be relevant to stroke pathophysiology (Du et al, 2017). Rat vs. mouse differences in inflammatory gene induction after focal brain ischemia have also been found in whole brain tissue (Schroeter et al, 2003; Zhou et al, 2016). Thus, although rodent models may not be completely predictive for human stroke, especially concerning the validation of immunomodulatory drugs (Sharp and Jickling, 2014), reproducibility of the results in more than one species significantly strengthens the translational value of preclinical evidence.…”
Section: Discussionmentioning
confidence: 93%